THE EFFECT OF HEALTH WORKERS' PERFORMANCE ON THE EFFECTIVENESS OF HEALTH SERVICES AT MAIWA PUBLIC HEALTH CENTER, ENREKANG REGENCY - A. Saniang; Pratiwi Ramlan; Sunandar Said; Mardhatillah (JTH: Journal of Technology and Health, 2026)
The performance of healthcare workers is an important factor influencing the effectiveness of healthcare services at community health centers (Puskesmas) as primary healthcare facilities. Improving healthcare workers' performance is essential to enhance service quality and meet community expectations. This study aimed to analyze the effect of healthcare workers' performance on the effectiveness of healthcare services at Maiwa Public Health Center, Enrekang Regency. A quantitative study with a cross-sectional design was conducted involving 98 respondents selected through accidental sampling from a population of 4,540 outpatient visitors. Data were collected using a structured questionnaire and analyzed through univariate analysis and simple linear regression using SPSS. The results showed that 51.0% of respondents assessed healthcare workers' performance as good, while 53.1% rated healthcare service effectiveness as good. Simple linear regression analysis revealed that healthcare workers' performance had a positive and significant effect on healthcare service effectiveness (p<0.05), with a coefficient of determination (R²) of 0.659, indicating that 65.9% of the variation in healthcare service effectiveness was explained by healthcare workers' performance. It can be concluded that improving healthcare workers' performance plays an important role in enhancing healthcare service effectiveness at Maiwa Public Health Center. Therefore, continuous performance evaluation and capacity development are necessary to improve service quality.